2019
DOI: 10.1002/14651858.cd003690.pub4
|View full text |Cite
|
Sign up to set email alerts
|

Pharmaceutical interventions for emotionalism after stroke

Abstract: Background Antidepressants may be useful in the treatment of abnormal crying associated with stroke. This is an update of a Cochrane Review first published in 2004 and last updated in 2010. Objectives To determine whether pharmaceutical treatment reduces the frequency of emotional displays in people with emotionalism after stroke. Search methods We searched the trial register of Cochrane Stroke (last searched May 2018). In addition, we searched the Cochrane Central Register of Controlled Trials (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 69 publications
0
18
0
Order By: Relevance
“…185 A recent Cochrane review that included seven RCTs concluded that antidepressants (including SSRIs and TCAs) reduce the frequency and severity of crying episodes, though the quality of evidence was low. 186 Dextromethorphan/quinidine, the only drug currently approved specifically for emotionalism, was recently reported to be efficacious and well tolerated in an open-label study of stroke patients. 187…”
Section: Emotionalismmentioning
confidence: 99%
“…185 A recent Cochrane review that included seven RCTs concluded that antidepressants (including SSRIs and TCAs) reduce the frequency and severity of crying episodes, though the quality of evidence was low. 186 Dextromethorphan/quinidine, the only drug currently approved specifically for emotionalism, was recently reported to be efficacious and well tolerated in an open-label study of stroke patients. 187…”
Section: Emotionalismmentioning
confidence: 99%
“…A reliable, valid scale will ensure post-stroke emotionalism is correctly detected and not confused with depression. 1 Post Stroke Emotionalism is characterised by lessening of ability to control emotional expression, in particular unheralded crying episodes not under personal control. 2,3 Developing a robust psychometric measure of emotionalism following stroke is an important development for stroke care.…”
Section: Introductionmentioning
confidence: 99%
“…1 There are reports of emotionalism following multiple sclerosis, 2 Parkinson's disease, 3 and amyotrophic lateral sclerosis, 4 but the condition is most prevalent following stroke. 5,6 The pathophysiological mechanisms underlying PSE have been the subject of much speculation. Several studies have implicated cortico-pontine-cerebellar circuit damage in the onset of the condition, specifically disruption to the cerebellum's role in modulating emotional responses and aligning them to fit contextual information from the cortex.…”
Section: Introductionmentioning
confidence: 99%
“…Antidepressant medication was shown to reduce frequency of uncontrolled crying in a Cochrane review. 5 The clinical benefits however are, at best, modest, and side effects are experienced in a significant proportion of patients who take them. It is for this reason that clinicians are advised to exercise caution when prescribing.…”
Section: Introductionmentioning
confidence: 99%